Long-term efficacy and safety of ruxolitinib versus best available therapy in polycythaemia vera (RESPONSE): 5-year follow up of a phase 3 study. Issue 3 (March 2020) - Kiladjian, Jean-Jacques; Zachee, Pierre; Hino, Masayuki; Pane, Fabrizio; Masszi, Tamas; Harrison, Claire N; Mesa, Ruben; Miller, Carole B; Passamonti, Francesco; Durrant, Simon; Griesshammer, Martin; Kirito, Keita; et al.
Summary: Background: Polycythaemia vera is a myeloproliferative neoplasm characterised by excessive proliferation of erythroid, myeloid, and megakaryocytic components in the bone marrow due to mutations in the Janus kinase 2 (JAK2) gene. Ruxolitinib, a JAK 1 and JAK 2 inhibitor, showed superiority over best available therapy in a phase 2 study in patients with polycythaemia vera who were resistant to or intolerant of hydroxyurea. We aimed to compare the long-term safety and efficacy of ruxolitinib with best available therapy in patients with polycythaemia vera who were resistant to or intolerant of hydroxyurea. Methods: We report the 5-year results for a randomised, open-label, phase 3 study (RESPONSE) that enrolled patients at 109 sites across North America, South America, Europe, and the Asia-Pacific region. Patients (18 years or older) with polycythaemia vera who were resistant to or intolerant of hydroxyurea were randomly assigned 1:1 to receive either ruxolitinib or best available therapy. Patients randomly assigned to the ruxolitinib group received the drug orally at a starting dose of 10 mg twice a day. Single-agent best available therapy comprised hydroxyurea, interferon or pegylated interferon, pipobroman, anagrelide, approved immunomodulators, or observation without pharmacological treatment. The primary endpoint, composite response (patients who achieved both haematocrit control without phlebotomy and 35% or more reduction from baseline in spleen volume) at 32 weeeks was previously reported. Patients receiving best available therapy could cross over to ruxolitinib after week 32. We assessed the durability of primary composite response, complete haematological remission, overall clinicohaematological response, overall survival, patient-reported outcomes, and safety after 5-years of follow-up. This study is registered with ClinicalTrials.gov, NCT01243944 . Findings: We enrolled patients between Oct 27, 2010, and Feb 13, 2013, and the study concluded on Feb 9, 2018. Of 342 individuals screened for eligibility, 222 patients were randomly assigned to receive ruxolitinib (n=110, 50%) or best available therapy (n=112, 50%). The median time since polycythaemia vera diagnosis was 8·2 years (IQR 3·9–12·3) in the ruxolitinib group and 9·3 years (4·9–13·8) in the best available therapy group. 98 (88%) of 112 patients initially randomly assigned to best available therapy crossed over to receive ruxolitinib and no patient remained on best available therapy after 80 weeks of study. Among 25 primary responders in the ruxolitinib group, six had progressed at the time of final analysis. At 5 years, the probability of maintaining primary composite response was 74% (95% CI 51–88). The probability of maintaining complete haematological remission was 55% (95% CI 32–73) and the probability of maintaining overall clinicohaematological responses was 67% (54–77). In the intention-to-treat analysis not accounting for crossover, the probability of survival at 5 years was 91·9% (84·4–95·9) with ruxolitinib therapy and 91·0% (82·8–95·4) with best available therapy. Anaemia was the most common adverse event in patients receiving ruxolitinib (rates per 100 patient-years of exposure were 8·9 for ruxolitinib and 8·8 for the crossover population), though most anaemia events were mild to moderate in severity (grade 1 or 2 anaemia rates per 100 patient-years of exposure were 8·0 for ruxolitinib and 8·2 for the crossover population). Non-haematological adverse events were generally lower with long-term ruxolitinib treatment than with best available therapy. Thromboembolic events were lower in the ruxolitinib group than the best available therapy group. There were two on-treatment deaths in the ruxolitinib group. One of these deaths was due to gastric adenocarcinoma, which was assessed by the investigator as related to ruxolitinib treatment. Interpretation: We showed that ruxolitinib is a safe and effective long-term treatment option for patients with polycythaemia vera who are resistant to or intolerant of hydroxyurea. Taken together, ruxolitinib treatment offers the first widely approved therapeutic alternative for this post-hydroxyurea patient population. Funding: Novartis Pharmaceuticals Corporation.